The kinetics of nanostructural relaxation in electrodeposited Ni upon low-temperature annealing: an in-situ X-ray diffraction investigation - Ze Chai; Zhiyuan Yu; Xiaoqi Chen (Journal of Materials Research and Technology, 2022)
The rather limited microstructural evolution in electrodeposited nanocrystalline Ni isothermally annealed at 453–493 K is investigated by using in situ X-ray diffraction technique. The nanostructural relaxation features roughly linear lattice contraction, based on which the kinetics analysis yields the activation energy of about 0.57 eV/atom, in good agreement with the fast diffusion of excess vacancies on the nonequilibrium surfaces and/or interfaces for Ni. The lattice contraction of Ni may result from a reduction in the grain boundary excess volume. The integral breadth of diffraction line profiles decreases with annealing time in an exponential manner, implying the gradual improvement of the lattice perfections during nanostructural relaxation. The microhardness evaluation demonstrates the initial invariance or slight softening and subsequent remarkable hardening of nanocrystalline Ni subjected to low-temperature annealing.